Editorial - Teodoro, António; Brás, José Viegas; Gonçalves, Maria Neves; Costa, António Pedro; Minayo, Maria Cecília Souza (Revista Lusófona de Educação, 2018)
Apresentação do nº 40 da Revista Lusófona de Educação